2018
DOI: 10.3847/1538-4357/aae07c
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Clouds Associated with the Type Ia SNR N103B in the Large Magellanic Cloud

Abstract: N103B is a Type Ia supernova remnant (SNR) in the Large Magellanic Cloud (LMC). We carried out new 12 CO(J = 3-2) and 12 CO(J = 1-0) observations using ASTE and ALMA. We have confirmed the existence of a giant molecular cloud (GMC) at V LSR ∼245 km s −1 towards the southeast of the SNR using ASTE 12 CO(J = 3-2) data at an angular resolution of ∼25 ′′ (∼6 pc in the LMC). Using the ALMA 12 CO(J = 1-0) data, we have spatially resolved CO clouds along the southeastern edge of the SNR with an angular resolution of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 54 publications
3
36
0
Order By: Relevance
“…This means that the expanding gas motion was possibly created by stellar winds or accretion winds from the progenitor system of the SNR (e.g. Sano et al 2017bSano et al , 2018Kuriki et al 2018), which gives alternative support for the physical association between the SNR shocks and the ISM. The minimum intensity spot corresponding to a geometric center of the expanding shell is l ∼ 159.…”
Section: Co and H I Analysis Resultsmentioning
confidence: 99%
“…This means that the expanding gas motion was possibly created by stellar winds or accretion winds from the progenitor system of the SNR (e.g. Sano et al 2017bSano et al , 2018Kuriki et al 2018), which gives alternative support for the physical association between the SNR shocks and the ISM. The minimum intensity spot corresponding to a geometric center of the expanding shell is l ∼ 159.…”
Section: Co and H I Analysis Resultsmentioning
confidence: 99%
“…Another source of the winds could be strong accretion outflows from the progenitor WD binary system prior to the SN explosion (Hachisu et al 1996). Windblown molecular bubbles have been reported for Type Ia SNR Tycho (Zhou et al 2016;Chen et al 2017) and N103B (Sano et al 2018). Dense wind bubbles have also been found in Type Ia SNR candidates RCW 86 (Williams et al 2011)…”
Section: Appendix B Gas Parameters and Snr Propertiesmentioning
confidence: 96%
“…. , 45 K km s −1 ), and indicate the potential molecular gas association found by Sano et al (2018). Four circles show regions containing optical nebula knots, as seen in the HST Hα emission (Li et al 2017) the Western hemisphere that is ∼ 3 times brighter than the Eastern hemisphere (Dickel and Milne 1995).…”
Section: Introductionmentioning
confidence: 93%
“…It is located close to a dense H II region (Chu and Kennicutt 1988), and only ∼ 40 pc from the young star cluster NGC 1850 (Li et al 2017). X-ray (Hughes et al 1995), CO (Sano et al 2018) and optical studies (Rest et al 2005(Rest et al , 2008 have shown that it is likely to be a type Ia SNR; Li et al (2017) observed a main sequence star that is likely to be the surviving companion. As shown in Fig.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation